PENGARUH MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA PADA MATA DIKLAT MENANGANI SURAT MASUK DAN KELUAR (MAIL HANDLING) - Nur Fadlillah, (Pendidikan Ekonomi, 2011)
The study is aimed to examine how students learning motivation influences their learning achievement in mail handling lesson. The tenth graders of office administration class at SMKN 1 Boyolangu, Tulungagung sampled were 74 students. The data were collected through questionnaires and the dataobtained were analyzed with the use of linier regression statistical method. The result indicates that the learning motivation of tenth-graders of SMKN 1 Boyolangu Tulungagung is high and the students learning achievement is good as well. The data analysis shows that learning motivation affects the students achievement by 60.7 % and other factors excluded in this study influenced by 39.3 %. Thus, the studentslearning motivation has a positive and significant influence on their achievement.